A comparative study on the mechanical, electrical and piezoresistive properties of polymer composites using carbon nanostructures of different topology. (February 2018) - Avilés, F.; May-Pat, A.; López-Manchado, M.A.; Verdejo, R.; Bachmatiuk, A.; Rümmeli, M.H.
Graphical abstract: Highlights: Nanocomposites with carbon nanostructures of different topology were examined. The electro-mechanical response of the polymer nanocomposites were investigated. The effect of hybrid carbon fillers was investigated. Correlations between nanostructure and effective property were constructed. The excluded volume theory is used to explain the piezoresistive response. Abstract: The mechanical properties, electrical conductivity and piezoresistive response of thermosetting polymer nanocomposites comprising carbon nanotubes (CNTs, one-dimensional topology, 1D), few-layer thermally reduced graphene oxide (FLG, two-dimensional topology, 2D), cubic-shaped few-layer graphene shells (CGSs, three-dimensional topology, 3D), and hybrid combinations of them (1D-2D and 1D-3D) are investigated. It is observed that the most electro-conductive materials are formed when CGSs, CNTs or a hybrid combination of both are used, likely because of the lower defect density of CGSs and the higher aspect ratio of CNTs. The mechanical properties and piezoresistive sensitivity are higher for composites comprising CNTs or a 1D-2D hybrid combination of CNTs and FLGs. While the increased mechanical properties for these two groups of composites are attributed to the higher aspect ratio/lateral size, higher number of dangling bonds and functionalities, and higher specific surface area (for the case of FLGs) of their fillers, the increased piezoresistive sensitivity is explained in terms of their higher excluded volume within the composite.